The Yin and Yang of Cytoreductive SBRT in Oligometastases and Beyond - Onderdonk, Benjamin E.; Chmura, Steven J. (Frontiers in Oncology, 2019)
Abstract: Background: Oligometastatic disease has emerged as a possibly distinct metastatic phenotype in numerous cancer histologies. With the advancement in treatment modalities including stereotactic body radiation therapy (SBRT), certain patients may derive benefits from local ablative therapy. SBRT alone has already shown to have potential benefits in certain oligometastatic disease types. However, more understanding of the immunologic modulation and microenvironment is needed to guide which patients may benefit from SBRT alone or with combination therapy, if at all. Purpose: The purpose of this review is to offer an update on the emerging data testing SBRT combined with immunotherapy, review the pro-inflammatory and immunosuppressive effects of the tumor microenvironment, discuss novel molecular targets used to augment the immune response, and review potential methods used to decrease toxicity in order to improve the therapeutic ratio.